Segmentation of Waste Management of All Provinces in Indonesia Using K-Means Clustering - Mad'hika, Yudha Randa; Pirman, Arif (Journal of Intelligent Decision Support System (IDSS), 2025)
The amount of waste in Indonesia continues to increase along with the increasing population and welfare. Waste data there are so many waste data throughout Indonesia that it is difficult to determine which managed waste data from provinces will be taken so a recommendation is needed to determine it. Mapping waste management based on the results of waste managed into animal feed raw materials, compost raw materials, recycled raw materials, up-cycle raw materials and energy source raw materials is expected to help the government (or local government) make more appropriate policies. Therefore, this research uses a clustering method, namely k-means clustering. Based on the results of the analysis using the elbow method, the optimal number of clusters selected in this study is k=2. Next, the process of clustering managed waste is carried out using the K-Means clustering algorithm. The clustering results on waste management data display data information with a low level of proportion of waste management volume consisting of 28 provinces and a high level of proportion of waste management volume consisting of 6 provinces. Based on the evaluation of the k-means clustering results, the maximum value of the silhouette coefficient = 0.940 and the Davies-Bouldin index value = 0.430. The concrete recommendations are to make the province with the highest proportion of waste management as a pilot project for the construction of PLTSa, develop a Public-Private Partnership scheme for investment in waste-to-energy processing technology and accelerate licensing and local regulations that support the operationalization of WtE.